IDENTIFIKASI KOLAGEN DARI CANGKANG BULU BABI (Diadema setosum) ASAL PERAIRAN PULAU LEMUKUTAN - Idiawati, Nora; Novita, Intan; Nurdiansyah, Sy. Irwan; Minsas, Sukal; Siregar, Sepridawati (Marinade, 2022)
The purpose of this study was to determine the results of the identification of sea urchin collagen on the quality of the yield produced and the absorption function group of FTIR (Fourier Transform Infra Red). The results of the analysis of the yield value of collagen extract using hydrochloric acid solvent concentration of 1 % was 0.49 %, 3 % was 0.76 %, 5 % was 0.62 %. Then additional collagen extraction was carried out at the concentration with the best results to identify the quality of the collagen. The identification results in the water content value of 21.31 %, ash content of 42.8 %, and the results of the FTIR (Fourier Transform Infra Red) wave number for Amide A of 3448.72 cm-1,Amide B of 2924.09 cm-1, Amide I of 1641.42 cm-1, Amide II of 1539.20 cm-1, Amide III of 1228.66 cm